2018
DOI: 10.1371/journal.pone.0197432
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening primary eye care in South Africa: An assessment of services and prospective evaluation of a health systems support package

Abstract: Visual impairment is a significant public health concern, particularly in low- and middle-income countries where eye care is predominantly provided at the primary healthcare (PHC) level, known as primary eye care. This study aimed to perform an evaluation of primary eye care services in three districts of South Africa and to assess whether an ophthalmic health system strengthening (HSS) package could improve these services. Baseline surveys were conducted in Cape Winelands District, Johannesburg Health Distric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…This was foreseeable, given the structure of the hospital. These individual, social, and organizational level barriers are consistent with those in the literature [12,[21][22][23]. Some hospitals are testing the effectiveness of conducting DR screening at the diabetes clinic to overcome this challenge [24].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This was foreseeable, given the structure of the hospital. These individual, social, and organizational level barriers are consistent with those in the literature [12,[21][22][23]. Some hospitals are testing the effectiveness of conducting DR screening at the diabetes clinic to overcome this challenge [24].…”
Section: Discussionsupporting
confidence: 64%
“…We therefore conclude that health system strengthening such as the development and implementation of clinical guidelines was a facilitator for the implementation of the intervention as well as adoption of screening behaviour by the participants. Several studies have found that health system strengthening gives traction to heath care interventions [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Most eye care providers (ophthalmologists and optometrists) in South Africa are with the private sector in the urban areas of the provinces, leaving minimal numbers in the public sector to cater for the majority of the populace [ 67 ]. Hence, with a considerable proportion of the people in poverty living in rural areas [ 68 ], coupled with the differences in the distribution of healthcare personnel, and the unavailability of eye care service providers in the rural areas as compared to the urban communities, make access to health care services extremely challenging and thus, may lead to increased prevalence of vision loss in the rural areas [ 69 72 ]. Furthermore, blurred vision and difficulty reading were the main contributors to vision loss in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a prospective study by Lilian et al, which assessed the primary eye care services in three South African districts, showed the need for introducing health system strengthening (HSS) package in primary eye care delivery. The study revealed that HSS enhanced organizational care and clinical practice [ 77 ]. Therefore, to curb the increasing occurrence of people going needlessly blind or having visual impairments, it is imperative that policymakers institute measures that aim to integrate ocular health promotional activities in the primary health care system.…”
Section: Discussionmentioning
confidence: 99%
“…Eye health promotion requires a holistic approach that empowers both individuals and communities [17] to take action for their eye health as well as strengthening sectoral partnerships at the district and national level. A prospective study [18] which evaluated primary eyecare services in three South African districts revealed that introducing a health system strengthening (HSS) package strengthened primary eyecare through improvement in organizational care and clinical practice. Therefore, assessing the patterns of eye care utilization is essential for appraising current eye health promotion systems [6,14].…”
Section: Introductionmentioning
confidence: 99%